Comparative Genomics Revealed Fluoroquinolone Resistance Determinants and OmpF Deletion in Carbapenem-Resistant Escherichia coli - Yang, Wan-Ting; Chiu, I-Ju; Huang, Yao-Ting; Liu, Po-Yu (Frontiers in Microbiology, 2022)
E. coli is a major causative organism of complicated urinary tract infection, blood stream infection and pneumonia. With the widespread use of antimicrobial agents, the prevalence of carbapenem resistance in E. coli is increasing with limited therapeutic option. Fluoroquinolone remains a choice in carbapenem resistant E. coli if susceptible, however, there are little information regarding the fluoroquinolone resistance mechanisms in carbapenem resistant E. coli. Complete genome sequencing and comparative genomics in the study detected gyrA D87N mutation fluoroquinolone resistance in carbapenem resistant E. coli. Moreover, deletion in OmpF (DEL264-269) was identified in non carbapenemase producing carbapenem resistant E. coli. Combination analysis of clinical and genomics characteristics suggest the highly diverse nature in the carbapenem resistant E. coli.